Mercurial > hg > Members > kono > Proof > category
changeset 236:e20b81102eee
Burroni equational equalizer definition done.
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Sun, 08 Sep 2013 05:54:27 +0900 |
parents | 8835015a3e1a |
children | 776cda2286c8 |
files | equalizer.agda |
diffstat | 1 files changed, 26 insertions(+), 22 deletions(-) [+] |
line wrap: on
line diff
--- a/equalizer.agda Sun Sep 08 04:55:01 2013 +0900 +++ b/equalizer.agda Sun Sep 08 05:54:27 2013 +0900 @@ -33,19 +33,20 @@ -- -- Flat Equational Definition of Equalizer -- -record Burroni { c₁ c₂ ℓ : Level} ( A : Category c₁ c₂ ℓ ) {c a b : Obj A} (f g : Hom A a b) : Set (ℓ ⊔ (c₁ ⊔ c₂)) where +record Burroni { c₁ c₂ ℓ : Level} ( A : Category c₁ c₂ ℓ ) {c a b : Obj A} (f g : Hom A a b) (e : Hom A c a) : Set (ℓ ⊔ (c₁ ⊔ c₂)) where field - α : {a b c : Obj A } → (f : Hom A a b) → (g : Hom A a b ) → Hom A c a + α : {a b c : Obj A } → (f : Hom A a b) → (g : Hom A a b ) → {e : Hom A c a } → Hom A c a γ : {a b c d : Obj A } → (f : Hom A a b) → (g : Hom A a b ) → (h : Hom A d a ) → Hom A d c - δ : {a b c : Obj A } → (f : Hom A a b) → Hom A a c - b1 : A [ A [ f o α {a} {b} {a} f g ] ≈ A [ g o α f g ] ] - b2 : {d : Obj A } → {h : Hom A d a } → A [ A [ ( α f g) o (γ {a} {b} {c} f g h) ] ≈ A [ h o α (A [ f o h ]) (A [ g o h ]) ] ] - b3 : A [ A [ α f f o δ {a} {b} {a} f ] ≈ id1 A a ] + δ : {a b c : Obj A } → {e : Hom A c a } → (f : Hom A a b) → Hom A a c + b1 : A [ A [ f o α {a} {b} {a} f g {id1 A a} ] ≈ A [ g o α {a} {b} {a} f g {id1 A a} ] ] + b2 : {d : Obj A } → {h : Hom A d a } → A [ A [ ( α {a} {b} {c} f g {e} ) o (γ {a} {b} {c} f g h) ] ≈ A [ h o α (A [ f o h ]) (A [ g o h ]){id1 A d} ] ] + b3 : A [ A [ α {a} {b} {a} f f {id1 A a} o δ {a} {b} {a} {id1 A a} f ] ≈ id1 A a ] -- b4 : {c d : Obj A } {k : Hom A c a} → A [ β f g ( A [ α f g o k ] ) ≈ k ] - b4 : {d : Obj A } {k : Hom A d c} → A [ A [ γ {a} {b} {c} {d} f g ( A [ α {a} {b} {c} f g o k ] ) o δ (A [ f o A [ α f g o k ] ] ) ] ≈ k ] + b4 : {d : Obj A } {k : Hom A d c} → + A [ A [ γ {a} {b} {c} {d} f g ( A [ α {a} {b} {c} f g {e} o k ] ) o ( δ {d} {b} {d} {id1 A d} (A [ f o A [ α {a} {b} {c} f g {e} o k ] ] ) )] ≈ k ] -- A [ α f g o β f g h ] ≈ h β : { d e a b : Obj A} → (f : Hom A a b) → (g : Hom A a b ) → (h : Hom A d a ) → Hom A d c - β {d} {e} {a} {b} f g h = A [ γ {a} {b} {c} f g h o δ (A [ f o h ]) ] + β {d} {e} {a} {b} f g h = A [ γ {a} {b} {c} f g h o δ {d} {b} {d} {id1 A d} (A [ f o h ]) ] open Equalizer open Burroni @@ -219,14 +220,14 @@ -- b4 is not yet done ---- -lemma-equ1 : {a b c : Obj A} (f g : Hom A a b) → - ( eqa : {a b c : Obj A} → (f g : Hom A a b) → {e : Hom A c a } { fe=ge1 : A [ A [ f o e ] ≈ A [ g o e ] ] } → Equalizer A e f g ) - → Burroni A {c} f g -lemma-equ1 {a} {b} {c} f g eqa = record { - α = λ f g → equalizer (eqa f g ) ; -- Hom A c a +lemma-equ1 : {a b c : Obj A} (f g : Hom A a b) → (e : Hom A c a ) → + ( eqa : {a b c : Obj A} → (f g : Hom A a b) → {e : Hom A c a } → Equalizer A e f g ) + → Burroni A {c} {a} {b} f g e +lemma-equ1 {a} {b} {c} f g e eqa = record { + α = λ {a} {b} {c} f g {e} → equalizer (eqa {a} {b} {c} f g {e} ) ; -- Hom A c a γ = λ {a} {b} {c} {d} f g h → k (eqa f g ) {d} ( A [ h o (equalizer ( eqa (A [ f o h ] ) (A [ g o h ] ))) ] ) (lemma-equ4 {a} {b} {c} {d} f g h ) ; -- Hom A c d - δ = λ {a} f → k (eqa f f) (id1 A a) (lemma-equ2 f); -- Hom A a c - b1 = fe=ge (eqa f g) ; + δ = λ {a} {b} {c} {e} f → k (eqa {a} {b} {c} f f {e} ) (id1 A a) (lemma-equ2 f); -- Hom A a c + b1 = fe=ge (eqa {a} {b} {a} f g {id1 A a}) ; b2 = lemma-b2 ; b3 = lemma-b3 ; b4 = lemma-b4 @@ -282,29 +283,32 @@ ------- α(f,g) γ(f,g,α(f,g)j) δ(fα(f,g)j) = α(f,g)j ------- γ(f,g,α(f,g)j) δ(fα(f,g)j) = j - eefg : {a b c : Obj A} (f g : Hom A a b) {e : Hom A c a} → Equalizer A e ( A [ f o equalizer (eqa f g) ] ) (A [ g o equalizer (eqa f g) ] ) + eefg : {a b c : Obj A} (f g : Hom A a b) {e : Hom A c a} → Equalizer A e ( A [ f o equalizer (eqa f g {id1 A a}) ] ) (A [ g o equalizer (eqa f g {id1 A a}) ] ) eefg f g {e} = eqa ( A [ f o equalizer (eqa f g) ] ) (A [ g o equalizer (eqa f g) ] ) lemma-b4 : {d : Obj A} {j : Hom A d c} → A [ - A [ k (eqa f g) (A [ A [ equalizer (eqa f g) o j ] o equalizer (eqa (A [ f o A [ equalizer (eqa f g) o j ] ]) (A [ g o A [ equalizer (eqa f g) o j ] ])) ]) + A [ k (eqa f g) (A [ A [ equalizer (eqa f g) o j ] o + equalizer (eqa (A [ f o A [ equalizer (eqa f g {e}) o j ] ]) (A [ g o A [ equalizer (eqa f g {e} ) o j ] ])) ]) (lemma-equ4 {a} {b} {c} f g (A [ equalizer (eqa f g) o j ])) o k (eqa (A [ f o A [ equalizer (eqa f g) o j ] ]) (A [ f o A [ equalizer (eqa f g) o j ] ])) (id1 A d) (lemma-equ2 (A [ f o A [ equalizer (eqa f g) o j ] ])) ] ≈ j ] lemma-b4 {d} {j} = let open ≈-Reasoning (A) in begin - ( k (eqa f g) (( ( equalizer (eqa f g) o j ) o equalizer (eqa (( f o ( equalizer (eqa f g) o j ) )) (( g o ( equalizer (eqa f g) o j ) ))) )) + ( k (eqa f g) (( ( equalizer (eqa f g) o j ) o equalizer (eqa (( f o ( equalizer (eqa f g {e}) o j ) )) (( g o ( equalizer (eqa f g {e}) o j ) ))) )) (lemma-equ4 {a} {b} {c} f g (( equalizer (eqa f g) o j ))) o - k (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) (id1 A d) (lemma-equ2 (( f o ( equalizer (eqa f g) o j ) ))) ) + k (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) (id1 A d) (lemma-equ2 (( f o ( equalizer (eqa f g) o j ) ))) ) ≈⟨ car ((uniqueness (eqa f g) ( begin equalizer (eqa f g) o j ≈↑⟨ idR ⟩ (equalizer (eqa f g) o j ) o id1 A d ≈⟨⟩ - ((equalizer (eqa f g) o j) o equalizer (eqa (f o equalizer (eqa f g) o j) (g o equalizer (eqa f g) o j))) + ((equalizer (eqa f g) o j) o equalizer (eqa (f o equalizer (eqa f g {e}) o j) (g o equalizer (eqa f g {e}) o j))) ∎ ))) ⟩ j o k (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) (id1 A d) (lemma-equ2 (( f o ( equalizer (eqa f g) o j ) ))) ≈⟨ cdr ((uniqueness (eqa (( f o ( equalizer (eqa f g) o j ) )) (( f o ( equalizer (eqa f g) o j ) ))) ( begin - equalizer (eqa (f o equalizer (eqa f g) o j) (f o equalizer (eqa f g) o j)) - ≈⟨ {!!} ⟩ + equalizer (eqa (f o equalizer (eqa f g {e} ) o j) (f o equalizer (eqa f g {e}) o j)) o id1 A d + ≈⟨ idR ⟩ + equalizer (eqa (f o equalizer (eqa f g {e}) o j) (f o equalizer (eqa f g {e}) o j)) + ≈⟨⟩ id1 A d ∎ ))) ⟩ j o id1 A d